Athribis (Atripe) im Kontext : die Stadt und der Tempel als religiöses und kulturelles Zentrum von der ptolemäischen Zeit bis zum Hochmittelalter : Akten der internationalen Tagung, Tübingen 7.-9. Juni 2022 - Müller, Marcus,; Teotino, Carolina, (Studien zur spätägyptischen Religion ;, 2024)
The last unexcavated stone sanctuary from the Greco-Roman period, the Temple of Athribis near Sohag in Middle Egypt, remained partially buried until the beginning of this century. The focus of the Athribis (Atripe) conference in context, held from June 7th to 9th, 2022 in Tubingen, was the large number of research results already achieved from different disciplines as well as future research strands. The associated conference proceedings, edited by Marcus Muller and Carolina Teotino-Tattko, are dedicated to these results and cover a wide range of topics in 19 contributions based on archaeological, philological, technical and religious-historical approaches. The investigations deal with the excavated temple rooms, inscriptions and the recovered individual finds and place them in the regional and supra-regional context. Studies of architecture, art history and various groups of materials from the material remains provide a great variety of insights into the construction of the temple, its chronology and ultimately the everyday lives of the residents at the time. The sanctuary in Athribis is a veritable witness to its multi-faceted fate, which can be felt not only in its rooms, walls and ceilings, but also in the archaeological findings and findings.